Corporate Governance and Transfer Pricing - Sophie Louis Laurent Andia; Yulius Kurnia Susanto (Media Bisnis, 2023)
The purpose of this research is to present also state the evidence empirically regarding the effect of, audit quality, multinationality, foreign ownership, tax avoidance, bonus mechanism, debt covenant, tunneling incentive, and company size on transfer pricing. The data collected in this research is Manufacutring Company that listed in Indonesia Stock Exchange (IDX) from period 2019 to 2021. The purposive sampling method is used in this research as the based to determine the result of samples with 55 companies are selected out of 168 companies data from period 2019 to 2021. The data were executed and analyzed by multiple linear regression method. The result of research showed that multinationality and foreign ownership have an effect to transfer pricing. Other than that audit quality, tax avoidance, bonus mechanism, debt covenant, tunneling incentive, and company size have not influence on transfer pricing. Multinational companies and owned by foreign parties tend to have stricter supervision so that the probability of transfer pricing is low.